A scoping review pembelajaran kimia berwawasan green chemistry: Strategi dan lingkup materi - Aqilatun Ni'mah (Jurnal Kajian Pendidikan IPA, 2025)
A Scoping Review of Green Chemistry-Oriented Chemistry Learning: Strategies and Content Scope. Green chemistry has become an important approach in the development of sustainable and environmentally ethical chemistry education. This study aims to map chemistry learning strategies that incorporate green chemistry perspectives, as well as the scope of chemistry content integrated within this approach. The method used is a scoping review involving several stages: topic determination, article search and selection, article analysis and synthesis, and conclusion drawing. The scoping review focuses on 15 selected scientific articles published between 2014 and 2024. The results show that the most dominant strategies are project-based learning, problem-based learning, and inquiry-based learning. Furthermore, the implementation of green chemistry principles is also reflected in chemistry laboratory practices. The chemistry topics most frequently associated with green chemistry principles include stoichiometry, redox reactions, environmental chemistry, and carbon compounds. These findings highlight the need to integrate green chemistry principles into the curriculum and teaching practices in order to foster students’ ecological awareness from an early stage.